2015
DOI: 10.1016/j.atherosclerosis.2015.09.036
|View full text |Cite
|
Sign up to set email alerts
|

The association of pulmonary function with carotid atherosclerosis in older Chinese: Guangzhou Biobank Cohort Study-CVD Subcohort

Abstract: Independent of smoking status, poor pulmonary function was dose-dependently associated with carotid atherosclerosis in older Chinese. (281 words).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 31 publications
3
15
2
Order By: Relevance
“…A study by Chae et al found that the amount of vascular calcification was associated with the extent of emphysema on computed tomography and airflow limitation (22). This is in contrast with a recent study from China on elderly smokers with airflow limitation that found no evidence that the association of pulmonary function with CIMT varied by smoking status (23). …”
Section: Discussioncontrasting
confidence: 99%
“…A study by Chae et al found that the amount of vascular calcification was associated with the extent of emphysema on computed tomography and airflow limitation (22). This is in contrast with a recent study from China on elderly smokers with airflow limitation that found no evidence that the association of pulmonary function with CIMT varied by smoking status (23). …”
Section: Discussioncontrasting
confidence: 99%
“…Observationally poorer intrauterine experiences, proxied by birth weight or premature birth, are adversely associated with many aspects of adult health, including poorer lung function [2][3][4][5][6] . Lung function contributes both directly to chronic diseases via lung diseases and indirectly as a cardiovascular-related risk factor 7,8 , with potentially a causal role of forced expiratory volume 9 .…”
mentioning
confidence: 99%
“…In 9 studies [19,23,25,26,34,35,37,42,43], we found a significantly higher CIMT in 726 COPD patients than in 2130 controls (MD: 0.10 mm; 95% CI: 0.04, 0.16; p ¼ 0.0007, Fig. 1A), with high detected heterogeneity (I 2 ¼ 94%, p < 0.0001).…”
Section: Cimt and Carotid Plaquesmentioning
confidence: 76%